Habilidades para la autorregulación del aprendizaje en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Gutierrez Romaina, Patricia (2022)
Describing the skills for self-regulation of learning in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon located in the city of Iquitos in the current year 2021 has been the main objective raised in the research. As a methodology, the descriptive type of research was adopted, applying the cross-sectional, field, and univariate design. The study population and sample were 92 initial education students from the fourth and fifth levels of the faculty of education. In order to obtain data, a questionnaire was used, which has been validated by experts, and the technique used has been the survey. The main conclusion of the research is that the level of learning self-regulation skills in initial education students in the Faculty of Education Sciences and Humanities is 48.9% in the moderate while in 51.1% it is located at the right level. No student is at the wrong level.